2000
DOI: 10.7863/jum.2000.19.4.237
|View full text |Cite
|
Sign up to set email alerts
|

Is a full bladder still necessary for pelvic sonography?

Abstract: The objective was to determine whether a full bladder is routinely necessary for a complete sonographic evaluation of the female pelvis. Over the course of 1 month, all women having a gynecologic sonogram were scanned initially transabdominally through a full bladder by the sonographer (standard images taken). A physician then joined the sonographer and scanned the patient transvaginally without prior knowledge of the findings seen transvesically. The physician finished the examination transabdominally, with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 7 publications
(15 reference statements)
0
13
0
1
Order By: Relevance
“…This advance allows the operator to place a high-frequency endocavitary ultrasound transducer in close proximity to target pelvic organs, thus improving image resolution and obviating the need for patients to have a full bladder before ultrasound examinations. 16 Ultrasound imaging has the added advantage of real-time imaging, which allows for the probing of pelvic organs to elicit patient's symptoms and thus correlate symptoms with specific pelvic anatomic locations. The practitioner therefore can gain crucial information about the degree and area of pain and mobility of organs in the pelvis and correlate the ultrasound findings with the physical examination.…”
Section: The Real-time Transvaginal Ultrasound Imagingmentioning
confidence: 99%
“…This advance allows the operator to place a high-frequency endocavitary ultrasound transducer in close proximity to target pelvic organs, thus improving image resolution and obviating the need for patients to have a full bladder before ultrasound examinations. 16 Ultrasound imaging has the added advantage of real-time imaging, which allows for the probing of pelvic organs to elicit patient's symptoms and thus correlate symptoms with specific pelvic anatomic locations. The practitioner therefore can gain crucial information about the degree and area of pain and mobility of organs in the pelvis and correlate the ultrasound findings with the physical examination.…”
Section: The Real-time Transvaginal Ultrasound Imagingmentioning
confidence: 99%
“…It has been suggested that transvaginal sonography may improve accuracy for antenatal diagnosis of placenta accreta by improving the near-field resolution of the interface between the placenta and the lower uterine segment, especially in cases of placenta previa or a posterior placenta 16. It has also been suggested that the accuracy of sonography could also be affected by the frequency of the abdominal transducer used (a higher frequency will improve spatial resolution for superficial structures) or by the degree of bladder filling, especially when transvaginal sonography is not used 17,18. The difference in the specificity of MRI could be due to the use of gadolinium.…”
Section: Discussionmentioning
confidence: 99%
“…Немало усилий приложено в области совершенства технологии и методологии проведения ТПУС. Вопросам использования метрических таблиц, цветного и пульсирующего доплера посвящены работы ряда авторов [43][44][45]. УЗ техника «трех треков» (ТТТ) разработана с целью простой, быстрой и точной идентификации топографии субъектов, расположенных в клетчатке промежности и области дна малого таза.…”
Section: анализ литературных данных и постановка задачи исследованияunclassified